Vegetable oils protect phycocyanin from thermal degradation during cooking of spirulina-based "crostini". (March 2021) - Niccolai, Alberto; Venturi, Manuel; Galli, Viola; Pini, Niccolò; Rodolfi, Liliana; Biondi, Natascia; Granchi, Lisa; Tredici, Mario R.
Abstract: Phycocyanin is a well-known bioactive pigment contained in cyanobacteria, such as Arthrospira platensis (commonly known as spirulina), and used in the food and beverage industry. One of the main problems that affects spirulina-based bakery products is phycocyanin degradation during cooking, being this pigment extremely sensitive to heat. The main goal of this work was to evaluate the protective effect against phycocyanin degradation of extra virgin olive (EVO) oil or sunflower oil, by applying thermal treatments directly on A. platensis F&M-C256 biomass and on A. platensis F&M-C256-based "crostini", as well as on phycocyanin powder. After cooking, A. platensis F&M-C256 "crostini" incorporated with EVO or sunflower oil (10g oil/100g of dough) maintained about 90% of the phycocyanin originally present in the cyanobacterial biomass. When pure tocopherol was added to the biomass in the same amounts, a significant protective effect against phycocyanin degradation was observed. Tocopherol contained in EVO and sunflower oils is the putative main responsible for the protective action against phycocyanin degradation. Therefore, the incorporation of vegetable oils into the dough can be a useful tool for the food industries that use A. platensis biomass and/or phycocyanin as a natural food coloring and bioactive component for bakery products. Highlights: Phycocyanin degradation is affected by temperature and time during thermal treatment. Vegetable oils protect phycocyanin during cooking in spirulina "crostini". Tocopherol is the putative responsible for protecting phycocyanin against degradation.